(untitled) (ACME, 2017)
To a large extent, the detractors of Pamela criticized Richardson’s focus on the body. Pamela’s actions and narrative style appeared to be motivated by her desire, namely, by her passions, traditionally located in the body. In particular, Pamela’s bodily identity undermined her authority as an impartial eyewitness, suggested that she could not act as a disinterested narrator and that her voice was not creditable enough to acquire public relevance. Responding to his critics, in Pamela II Richardson set up a different narrative technique, and inscribed the body of the heroine with new, less problematic meanings. In Pamela II, there is a chronological gap between story and discourse. Moreover, in keeping with the codes and stereotypes of sensibility, Pamela is deeply moved by virtuous behaviour, her bodily reactions signalizing her moral value. Along with the new representation of the body goes the effacement of desire and, inevitably, the disintegration of plot. However, Richardson’s experimentation with narrative was not yet over. Reconciling disinterestedness and desire, in Clarissa he wove a polyphony of epistolary voices, enabling the disinterested assessment of an external interpreter.